Data archiving and sharing - Magle, C. Tobin, speaker (Colorado State University. Libraries, 2017)
This month's Data and Donuts will cover best practices for preparing your data for archiving. We will discuss how to properly describe your data so that others, or you from 5 years from now, will know what it is and how to use it, as well as appropriate places to store it. We'll also discuss options for repositories that will allow others to access your research data, including CSU's digital repository.
Data and donuts
Multiple sessions held on: 5/10/17, 7/25/17, 5/15/18.
Accessibility features: Transcript.
Keywords: data management; data preservation; data storage; data education; data archiving; Data curation